Między czasem ekologicznym a ekologią czasu w kulturze przyspieszenia - Strzelecka, Celina (Studia Etnologiczne i Antropologiczne, 2017)
Time and space are concepts that form an indivisible entity in the concept of ecological time. The process of separating these ideas in Anglo-American culture began along with the acceleration of technological development. It resulted in a quick, almost instantaneous rate of life, which affects destructively both individuals and general public. What is the main postulate of the ecology of time is to stop the negative effects of acceleration, and re-integrating the idea of time and space in the practice of everyday life.